Analysis of Feasibility, Adherence, and Appreciation of a Newly Developed Tele-Rehabilitation Program for People With MCI and VCI - Mosca, Irene Eleonora; Salvadori, Emilia; Gerli, Filippo; Fabbri, Laura; Pancani, Silvia; Lucidi, Giulia; Lombardi, Gemma; Bocchi, Leonardo; Pazzi, Stefania; Baglio, Francesca; Vannetti, Federica; Sorbi, Sandro; et al. (Frontiers in Neurology, 2020)
Background: patients with Mild Cognitive Impairment (MCI) and Vascular Cognitive Impairment (VCI) are at high risk of progressing to dementia. Recent guidelines indicate the importance of promoting multidimensional and multi-domain interventions to prevent further decline. Since the comparable effectiveness to conventional face-to-face interventions, the use of technology is gaining relevance. Tele-rehabilitation systems have the potential to engage patients in multi-dimensional activity programs and to guarantee a low-cost continuum of care through remote control. A possible limitation of such programs is represented by the lack of familiarization with technology and computers in olders. The purpose of this study is to describe the feasibility, adherence, and appreciation of the GOAL Tele-R system, administered by a web-application through remote control in patients with MCI/VCI. Methods: feasibility of the Tele-R system was evaluated by means of distribution of patients’ attrition along the study phases, controlling for potential systematic bias in drop-out rates due to the technological device. Adherence was evaluated analyzing drop-out rates and indexes of carried out activities. Patients’ appreciation was analyzed through an ad hoc satisfaction questionnaire items. Results: out of 86 approached patients, 25 (29%) were not enrolled, 30 (35%) dropped-out after randomization, and 31 (36%) completed the study (standard care group n=12, the tele-R group n=19). Compared to the tele-R group, rates of drop-outs resulted significantly higher for the standard care group (34% vs. 62%, respectively, p= .029). Taking into account baseline characteristics, females resulted in a statistically significant higher rates of drop-outs compared to males (66% vs. 27%, respectively, p= .003). Overall adherence to the proposed activities was 84% (85% for cognitive module and 83% for physical activity module). Concerning satisfaction, participants provided a good mean level of appreciation (3.7±0.8, range 1-5), a positive feedback for usability, and a subjective perception of cognitive, emotional and physical benefits due to the training. Conclusion: The GOAL Tele-R system seems a feasible technological rehabilitation program, reaching an acceptable level of adherence and appreciation in patients with MCI/VCI condition.